The Contribution of Parenting to the Social-Emotional Development of 4-5-Year-Old Children at Aisyiyah Pucangan Kartasura Kindergarten - Karuniawati, Elmi; Fauziyah, Nur (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study analyzes how different parental parenting styles—authoritarian, permissive, and democratic—contribute to the social‐emotional development of 4–5‑year‑old children at Aisyiyah Pucangan Kartasura Kindergarten, with a focus on skills such as empathy, cooperation, and emotional regulation. Methodology: Using a descriptive qualitative approach, data were collected through classroom and home observations, semi‑structured interviews with teachers and parents, and documentation of parent–teacher communications. Participants included kindergarten teachers and Group A children along with their parents, ensuring a comprehensive view of both home and school influences on child development. Results: The findings indicate that democratic parenting most effectively supports children’s social‐emotional growth, fostering empathy, cooperative behaviors, and self‐regulation. Although many parents reported practicing a democratic style, observations revealed occasional tendencies toward permissiveness or authoritarianism—either pampering or pressuring children during activities. Active parental involvement at home and in school events emerged as a critical factor in enhancing social‐emotional skills. Additionally, teacher‐designed play activities proved effective in stimulating critical thinking and creativity. Applications/Originality/Value: By highlighting the interplay between parenting styles and structured school activities, this research underscores the importance of consistent, collaborative partnerships between parents and teachers. Its insights advocate for improved communication channels and joint training programs to ensure cohesive, supportive environments that optimize children’s social‐ emotional and cognitive development.